Medical examinations of seafarers and training for medical doctors in maritime health - Heikki, S. (Актуальні проблеми транспортної медицини, 2005)
В соответствии с международными правилами врачи, работающие в области морской медицины, должны иметь специальную подготовку по профпатологии.Международному сотрудничеству врачей в области морской медицины уделяется внимание со стороны многих организаций. Международное сотрудничество в области морской медицины должно строиться на основе этических норм. Международная ассоциация морской медицины (ММАМ - IMHA) может стать той инстанцией, которая начнет международную дискуссию среди специалистов по вопросам проведения профессиональных отборов. ММАМ должна также организовать международные унифицированные курсы по подготовке врачей в области морской медицины и проведению профессиональных отборов моряков. Курсы, организованные в различных странах по всему миру с привлечением курсантов из разных стран, должны сократить существующий в настоящее время значительный разброс в стандартах проведения профосмотров, критериях подбора и медицинского обслуживания моряков. According to the international rules and regulations doctors working in maritime medicine need training in occupational medicine. The doctors must know: - National and international rules and regulations; - Work and life on board ship; - Health and fitness demands of the work on board ship; - Medical examination procedure; - Ethics in maritime medicine; - Risk evaluation procedure, when a seafarer has a disease; - Health promotion among seafarers International cooperation between medical doctors in maritime medicine has been stressed by international bodies. Ethical rules are needed to form the basis for successful work in international maritime medicine. The International Maritime Health Association (IMHA) could be a suitable forum to start an international discussion among specialists about facts, evidence and principles in medical examinations. IMHA should also organise international, unified training courses for medical doctors in maritime medicine, and in seafarers' fitness evaluation. Training, organized in various countries around the world with international students would diminish the existing wide variation in medical examinations, fitness criteria and medical care of seafarers.